Enhancing resilient community decision-making using building performance simulation. (15th January 2021) - Hopfe, Christina J.; McLeod, Robert S.
Abstract: It is widely acknowledged that faced with diverse future impacts (including extreme weather events, economic instability, energy supply vulnerabilities and pandemics) buildings and communities' worldwide need to become increasingly resilient. The work presented in this paper investigates how Community Design and Decision Making (CDDM) processes can be enhanced using smart decision making techniques involving Building Performance Simulation (BPS). This work presents action research based on findings from a real-world case study project involving the design of a mixed-use zero carbon community centre, planned for the Findhorn Eco-Community, in Scotland, UK. Throughout the conceptual and early design stages the community played a crucial part in the decision-making process. BPS results coupled with the use of sensitivity analysis (SA) techniques incorporating resilience as a performance criterion contributed to establishing a multi-criteria evidence base from which to inform the CDDM process. Although not yet fully implemented in commercial simulation tools, the approaches used (e.g. uncertainty analysis, using resilience as a performance objective) proved to be invaluable in informing and facilitating the CDDM process. Overall an integrated two-way communication process (using BPS and uncertainty analysis for decision support) enabled the community to play an informed role in the design decision-making process. Highlights: Building simulation is poorly integrated in Community Design and Decision Making (CDDM). Action research was used to assess building simulation in designing a zero-carbon community centre. Resilience was evaluated as a design objective using smart decision making and building simulation. Expert explanation of the 'how and why' of simulation facilitated acceptance of building simulation. When used transparently building simulation showed great potential to enhance the CDDM process.